Pharmacotherapy in inherited and acquired ventricular arrhythmia in structurally normal adult hearts. (22nd November 2019) - Ortmans, Staniel; Daval, Charline; Aguilar, Martin; Compagno, Pablo; Cadrin-Tourigny, Julia; Dyrda, Katia; Rivard, Lena; Tadros, Rafik
ABSTRACT: Introduction : Ventricular arrhythmias are often seen in association with structural heart disease. However, approximately a tenth of affected patients have apparently normal hearts, where such arrhythmias typically occur in young patients, are sometimes inherited and can occasionally lead to sudden cardiac death (SCD). Over the past two decades, increased understanding of the underlying pathophysiology resulted in improved targeted pharmacological therapy. Areas covered : This article reviews current knowledge regarding drug therapy for inherited arrhythmia syndromes (Brugada, early repolarization, long QT and short QT syndromes, and catecholaminergic polymorphic ventricular tachycardia), and acquired arrhythmias (idiopathic ventricular fibrillation, short-coupled torsade de pointes, outflow tract ventricular tachycardia, idiopathic left, papillary muscle and annular ventricular tachycardias). Expert opinion : In inherited arrhythmia syndromes, appropriate clinical and genetic diagnoses followed by proper selection and dosing of antiarrhythmic drugs are of utmost importance to prevent SCD, most often without the need of implantable cardioverter-defibrillators. In acquired arrhythmias, appropriate pharmacotherapy in selected patients can also provide symptomatic relief and avoid the need for invasive therapy. Further research is needed to develop novel antiarrhythmic drugs or targeted therapy to increase efficacy and limit side effects.